Tea and Its Components Prevent Cancer: A Review of the Redox-Related Mechanism - Mao, Xiangbing (Int J Mol Sci, 2019)
Cancer is a worldwide epidemic and represents a major threat to human health and survival. Reactive oxygen species (ROS) play a dual role in cancer cells, which includes both promoting and inhibiting carcinogenesis. Tea remains one of the most prevalent beverages consumed due in part to its anti- or pro-oxidative properties. The active compounds in tea, particularly tea polyphenols, can directly or indirectly scavenge ROS to reduce oncogenesis and cancerometastasis. Interestingly, the excessive levels of ROS induced by consuming tea could induce programmed cell death (PCD) or non-PCD of cancer cells. On the basis of illustrating the relationship between ROS and cancer, the current review discusses the composition and efficacy of tea including the redox-relative (including anti-oxidative and pro-oxidative activity) mechanisms and their role along with other components in preventing and treating cancer. This information will highlight the basis for the clinical utilization of tea extracts in the prevention or treatment of cancer in the future.